Compreensão dos aspectos funcionais no Para Taekwondo: uma investigação sobre equilíbrio durante testes de chutes consecutivos com restrições de membros superiores - Oliveira, Raphaela Alves Feitosa de (2023)
Olympic Taekwondo (TKD) is an Olympic sport characterized by high-amplitude high kicks, intermittent and high-intensity actions in unipodal standing. These kicks require maximum postural control and anaerobic performance. Para Taekwondo (PTKD), on the other hand, is an adaptation of Olympic TKD aimed at people with disabilities (PCD). In order to minimize the impact of the disability and encourage sports practice, para-athletes are classified into sports categories. To determine these classes, physical and functional tests are required. Functioning in these cases is measured by looking at issues relating to muscle strength, power and range of movement. Currently in PTKD para-athletes are allocated to classes K43 (bilateral amputation - elbow to hand joint) and K44 (unilateral or bilateral arm amputation). However, there is a gap in the literature about the impact of the absence of the upper limb on the training and assessment process of PTKD para-athletes. Our study started from the premises that the absence of limbs influences the ability to balance during consecutive kicks. Thus, we investigated whether balance is influenced by the performance of consecutive kicking tests with upper limb restrictions. To this purpose, nine Taekwondo practitioners were randomized into three situations: baseline (no restriction), restriction of dominant MS, non-dominant MS and total restriction (both MS). The participants were allocated to the above situations and performed the following protocol at the Pre (Subjective Perception of Recovery [PSR] - Stabilometry - Countermovement Jump [CMJ]) and Post (CMJ - Stabilometry - Subjective Perception of Effort [PSE]) moments. The Anaerobic Intermittent Kick Test (TAIKT) was used to test the participants' anaerobic performance. The results indicated that there were differences in anterior-posterior balance after TAIKT (F3.32 = 0.351; p = 0.026; η2G = 0.111). The other variables showed no differences when comparing pre vs. post. We conclude that balance is not influenced by the consecutive kick test. Our study contributes to a better understanding of the assessment of functional aspects in para-athletes, expanding knowledge in the field of Physiotherapy and Physical Education, especially in the processes of promotion, performance and functional recovery of individuals with amputation.